Answer:
6, 24, 96, 384
Step-by-step explanation:
a₁ = 6
a₂ = 4 x a₁ = 4 x 6 = 24
a₃ = 4 x a₂ = 4 x 24 = 96
a₄ = 4 x a₃ = 4 x 96 = 384
Answer:
See below
Step-by-step explanation:
1)
![\frac{11 + x}{(2 - x)(x - 3)} = \frac{A}{2 - x} + \frac{B}{x - 3} \\ \\ \therefore \: \frac{11 + x}{(2 - x)(x - 3)} = \frac{A(x - 3) +B(2 - x) }{(2 - x)(x - 3)} \\ \\ \therefore \: 11 + x = Ax - 3A + 2B - Bx \\ \\ \therefore \: 11 + x = - 3A + 2B + Ax - Bx\\ \\ \therefore \: 11 + x = - 3A + 2B + (A - B)x \\ \\ equating \: the \: like \: terms \: on \: both \: sides \\ A - B = 1 \\ \therefore \: A = B + 1.....(1) \\ \\ - 3A + 2B = 11....(2) \\ from \: eq \: (1) \: and \: (2) \\ - 3(B + 1) + + 2B = 11 \\ \\ - 3B - 3 + 2B = 11 \\ \\ - B = 11 + 3 \\ \\ B = - 14 \\ A = - 14 + 1 = - 13 \\ \\ \frac{11 + x}{(2 - x)(x - 3)} = \frac{ - 13}{2 - x} + \frac{ - 14}{x - 3} \\ \\ \frac{11 + x}{(2 - x)(x - 3)} = - \frac{ 13}{2 - x} - \frac{ 14}{x - 3}](https://tex.z-dn.net/?f=%20%5Cfrac%7B11%20%2B%20x%7D%7B%282%20-%20x%29%28x%20-%203%29%7D%20%20%3D%20%20%5Cfrac%7BA%7D%7B2%20-%20x%7D%20%20%2B%20%20%5Cfrac%7BB%7D%7Bx%20-%203%7D%20%20%5C%5C%20%20%5C%5C%20%20%5Ctherefore%20%5C%3A%20%20%5Cfrac%7B11%20%2B%20x%7D%7B%282%20-%20x%29%28x%20-%203%29%7D%20%20%3D%20%20%5Cfrac%7BA%28x%20-%203%29%20%2BB%282%20-%20x%29%20%7D%7B%282%20-%20x%29%28x%20-%203%29%7D%20%20%20%5C%5C%20%20%5C%5C%20%5Ctherefore%20%5C%3A%20%2011%20%2B%20x%20%3D%20Ax%20-%203A%20%2B%202B%20-%20Bx%20%5C%5C%20%20%5C%5C%20%20%5Ctherefore%20%5C%3A%2011%20%2B%20x%20%3D%20-%203A%20%20%2B%202B%20%20%2B%20Ax%20-%20%20Bx%5C%5C%20%20%5C%5C%20%20%5Ctherefore%20%5C%3A%2011%20%2B%20x%20%3D%20-%203A%20%20%2B%202B%20%20%2B%20%28A%20-%20B%29x%20%5C%5C%20%20%5C%5C%20equating%20%5C%3A%20the%20%5C%3A%20like%20%5C%3A%20terms%20%5C%3A%20on%20%5C%3A%20both%20%5C%3A%20sides%20%5C%5C%20A%20-%20B%20%3D%201%20%5C%5C%20%20%5Ctherefore%20%5C%3A%20A%20%20%3D%20%20B%20%20%2B%20%201.....%281%29%20%5C%5C%20%20%5C%5C%20%20-%20%203A%20%20%2B%202B%20%3D%2011....%282%29%20%5C%5C%20%20from%20%5C%3A%20eq%20%5C%3A%20%281%29%20%5C%3A%20and%20%5C%3A%20%282%29%20%5C%5C%20%20-%203%28B%20%20%2B%20%201%29%20%2B%20%2B%202B%20%3D%2011%20%5C%5C%20%20%5C%5C%20-%203B%20%20%20-%203%20%20%2B%202B%20%3D%2011%20%5C%5C%20%20%5C%5C%20%20-%20B%20%3D%2011%20%2B%203%20%5C%5C%20%20%5C%5C%20B%20%3D%20%20-%2014%20%20%5C%5C%20A%20%20%3D%20%20%20-%2014%20%2B%20%201%20%3D%20%20-%2013%20%5C%5C%20%20%5C%5C%20%20%5Cfrac%7B11%20%2B%20x%7D%7B%282%20-%20x%29%28x%20-%203%29%7D%20%20%3D%20%20%5Cfrac%7B%20-%2013%7D%7B2%20-%20x%7D%20%20%2B%20%20%5Cfrac%7B%20-%2014%7D%7Bx%20-%203%7D%20%5C%5C%20%20%5C%5C%20%5Cfrac%7B11%20%2B%20x%7D%7B%282%20-%20x%29%28x%20-%203%29%7D%20%20%3D%20-%20%20%20%5Cfrac%7B%2013%7D%7B2%20-%20x%7D%20%20%20-%20%20%5Cfrac%7B%2014%7D%7Bx%20-%203%7D)
2)
![\therefore \frac{12x + 11}{x^2 +x - 6}=\frac{A}{(x +3)}+\frac{B}{(x - 2)}](https://tex.z-dn.net/?f=%20%5Ctherefore%20%5Cfrac%7B12x%20%2B%2011%7D%7Bx%5E2%20%2Bx%20-%206%7D%3D%5Cfrac%7BA%7D%7B%28x%20%2B3%29%7D%2B%5Cfrac%7BB%7D%7B%28x%20-%202%29%7D)
Equating like terms on both sides:
Solving equations (1) & (2), we find:
A = 5, B = 7
![\therefore \frac{12x + 11}{x^2 +x - 6}=\frac{5}{(x +3)}+\frac{7}{(x - 2)}](https://tex.z-dn.net/?f=%20%5Ctherefore%20%5Cfrac%7B12x%20%2B%2011%7D%7Bx%5E2%20%2Bx%20-%206%7D%3D%5Cfrac%7B5%7D%7B%28x%20%2B3%29%7D%2B%5Cfrac%7B7%7D%7B%28x%20-%202%29%7D)
B is correct.
A. 5(x-2)= 5x-10
B. 4(x+3)= 4x + 12
C. 3(x+1)= 3x+3
D. 2(x+7) = 2x + 14
Answer:
D) (x - 2)(x² - 8)
Step-by-step explanation:
Separate the polynomial into two groups of two terms and factor out the common value from each group. If the values factored out from each group are the same, then you can use the grouping method. The factors will be the outside terms and the common factor.
x³ - 2x² + -8x + 16
= x²(x - 2) + -8(x - 2)
= (x² - 8)(x - 2)
Answer:
x= -8, y= -6/5, z= -6
Step-by-step explanation:
that is the answer